2016
DOI: 10.1093/nar/gkw523
|View full text |Cite
|
Sign up to set email alerts
|

Integration of TP53, DREAM, MMB-FOXM1 and RB-E2F target gene analyses identifies cell cycle gene regulatory networks

Abstract: Cell cycle (CC) and TP53 regulatory networks are frequently deregulated in cancer. While numerous genome-wide studies of TP53 and CC-regulated genes have been performed, significant variation between studies has made it difficult to assess regulation of any given gene of interest. To overcome the limitation of individual studies, we developed a meta-analysis approach to identify high confidence target genes that reflect their frequency of identification in independent datasets. Gene regulatory networks were ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
550
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 291 publications
(577 citation statements)
references
References 76 publications
(135 reference statements)
26
550
1
Order By: Relevance
“…A strong candidate for such a factor is the DREAM complex, which represses G 1 /S-expressed cell cycle genes in a p21-dependent manner (26,54). We noticed frequent downregulation of DREAM complex targets in Ki-67-depleted cells, which led us to test whether sensitivity to Ki-67 depletion was also p21 dependent.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A strong candidate for such a factor is the DREAM complex, which represses G 1 /S-expressed cell cycle genes in a p21-dependent manner (26,54). We noticed frequent downregulation of DREAM complex targets in Ki-67-depleted cells, which led us to test whether sensitivity to Ki-67 depletion was also p21 dependent.…”
Section: Discussionmentioning
confidence: 94%
“…As a CDK inhibitor (32,33), p21 blocks CDK-mediated Rb phosphorylation, thereby inhibiting E2F-driven transcription (56). Likewise, it maintains the activity of the transcriptionally repressive DREAM complex, which contains Rb-related p107/p130 "pocket protein" subunits (26,27,54). p21 also directly interacts with PCNA and directly inhibits DNA synthesis (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the reported role of Cdh1 in Ki67 degradation (Sobecki et al, 2016), we found that knockdown of Cdh1 (FZR1) via small interfering RNA (siRNA) resulted in the reduced degradation of Ki67 in G1 and overall elevated Ki67 levels (Figure 4C), supporting the notion that APC/C Cdh1 mediates degradation of Ki67 in G1. The Ki67 gene promoter harbors a CHR motif that binds the MMB (Myb-MuvB) complex (Sadasivam and DeCaprio, 2013), and the Ki67 promoter has been consistently pulled down in several chromatin immunoprecipitation sequencing (ChIP-seq) experiments by multiple components of the MMB complex (Fischer et al, 2016). Therefore, we knocked down two different transcription factors of the MMB complex, MYBL2 (B-Myb) and FOXM1 .…”
Section: Resultsmentioning
confidence: 99%
“…2). A subset of DREAM targets is also bound by FOXM1, controlling expression of genes in G2/M (Fischer et al 2016). The identification of putative CDE/CHR motifs within the promoters of CENP-A and HJURP (Fig.…”
Section: Discussionmentioning
confidence: 99%